Populism in Peru: Populist attitudes and perception of the populist offer and its relationship with political cynicism and attitudes toward democracy - Espinosa, Agustin; Janos, Erika; Pacheco, Manuel; Juárez, Juan; Chaparro, Hernán (Frontiers in Psychology, 2022)
Populism is a phenomenon that is gaining attention in Political Psychology. The goal of the current study was to determine the relationship between populist attitudes, based on demand and perception of the populist offer, and several indices of political cynicism and democratic attitudes in Peru. To do this, a quantitative correlational study including 391 participants from diverse Peruvian locations was carried out. Both populist attitudes and critical perception of the populist offer are found to be directly related to political cynicism in its dimensions of generalized distrust, despair over corruption, and political moral laxity, and inversely related to the dimension of willingness to change the system. Similarly, both dimensions of populism are directly related to democratic support and inversely related to democratic satisfaction. The findings support the notion that populist attitudes emerge in the context of distrust of the system and express an ambivalent relationship with democracy. Furthermore, the various approaches developed by the social sciences to address the populist phenomenon are discussed in terms of their strengths and limitations.